Bridging the AI Explainability Gap in Cardiac Imaging: A Review of Hybrid Approaches Using Grad-CAM and SHAP - Umar Sani Dabai (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The growing adoption of deep learning within the domain of medical imaging has yielded substantial enhancements in the capabilities of computer-assisted diagnosis and prognosis. However, the ability to interpret and explain the decisions made by these models continues to pose a significant obstacle, which impedes their successful integration into clinical practice. This review paper explores a hybrid approach that leverages the Gradient-weighted Class Activation Mapping technique and the Shapley Additive Explanations technique to bridge the artificial intelligence explainability gap in cardiac imaging. The paper discusses the strengths and limitations of these techniques, their application in cardiac imaging, and the potential for integrating them into a machine learning pipeline for robust and trustworthy artificial intelligence systems. Furthermore, it emphasizes the significance of developing artificial intelligence systems that are clinically translatable, addressing the explainability gap between clinical experts and non-experts. This ensures wider inclusion of diverse stakeholders involved in patient care, ultimately leading to improved patient outcomes and enhanced trust in AI-driven healthcare solutions.